Applied Gis software for improving pedestrian & bicycle safety - Ziari, Hasan; Khabiri, Mohammed M. (Transport, 2005)
People are important in towns. They are the foundation of the social and economic processes that drive the urban system and sustain the urban fabric. While people spend much of their time inside buildings – at home, at work, and at play – it is the movement of people, whether in vehicles or on foot, that is indicative of the vibrancy of the town. Comfort and safety are important for people movement. The crash data in cities, provinces started with the Traffic Organization of Inner Ministry looking at access management controls on functionally classified streets. Safety is a driving factor in access management and the crash reports are the best indicator of the lack of safe roads. This paper presents the development and findings of crash data from police reports and how they are being used in Geographic Information System (GIS). This tool generates a contour map identifying areas of high crash occurrence determined by crash density and clusters of crashes involving pedestrians or bicyclists. Summary statistics of the selected zones can be generated and displayed in a table or chart form.First Published Online: 27 Oct 2010